2010
DOI: 10.1136/bcr.07.2009.2113
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia associated with cardiac tamponade and chronic fluid excess

Abstract: SummaryWe describe a complex case of hyponatraemia with two aetiologies. A 49-year-old man who drank 6 litres of dilute alcohol per day presented confused and oedematous with a serum sodium of 95 mmol/litre. Urine sodium was <10 mmol/litre and urine osmolality 440 mOsmol/kg. Chest x-ray demonstrated a globular heart. ECG showed saddle-shaped ST elevation. ECHO demonstrated a large pericardial effusion causing marked tamponade. Following pericardiocentesis there was a marked diuresis; serum sodium returned to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Pericardial effusion-associated hyponatremia has been described in previous case reports [2][3][4][5][6] and retrospective studies [7,8]. In most patients, hyponatremia resolves following medical management or pericardiocentesis.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Pericardial effusion-associated hyponatremia has been described in previous case reports [2][3][4][5][6] and retrospective studies [7,8]. In most patients, hyponatremia resolves following medical management or pericardiocentesis.…”
Section: Discussionmentioning
confidence: 90%
“…Resolution of hyponatremia following pericardiocentesis has been described in case reports by other authors [2][3][4][5][6]. In addition, in a recent review of 31 patients, Jong et al found that individuals with cardiac tamponade-related hyponatremia demonstrated a statistically significant increase in serum sodium levels within 48 hours of pericardiocentesis [7].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations